Reconceptualizing international investment law from the Global South" by Fabio Morosini and Michelle Ratton Sanchez Badin - LIU, Han-wei (Institutional Knowledge at Singapore Management University, 2018)
This volume, edited by Fabio Morosini and Michelle Ratton Sanchez Badin, the leading legal academics from Brazil, features nine chapters written by highly regarded scholars in the area of international economic law. This book distinguishes itself from the existing scholarship in several important ways.